Dystopia and Anti-utopia: Genre Structure in the Novel The Day I Picked the Flower (Preučevanje otroške in mladinske književnosti, 2025)
Jasminka Tihi-Stepanić is a Croatian author who focuses on writing children’s and young adult literature. This paper interprets her latest novel, The Day I Picked the Flower (2023). Since the story takes place in a futuristic world where everything is prescribed and predetermined, the paper begins by defining the concepts of utopia, dystopia and anti-utopia to clarify terminological confusion. Based on the previous theoretical insights about genre issues, the paper explores formal, thematic, and rhetorical dimensions of the genre, demonstrating how their mutual connection shapes the dystopian genre in Tihi-Stepanić’s novel. The distinction between anti-utopia and dystopia is emphasized by separating and analysing typical thematic features of dystopian novels. The book The Day I Picked the Flower classifies as a classical dystopia.